The Effectiveness of VR Cuisine as a Teaching Aid for Special Needs Students Culinary Basic Certificate of Selayang Community College, Malaysia - Syariza Binti Mohamad Samuri; Fazlilawati Binti Fadzil; Mohd Khaidir Bin Che Hassan (Department of Special Education, 2021)
Teaching and learning methods for students with special needs require a new approach to attract interest, increase motivation and help strengthen memory. Game-based learning using VR Cuisine is a 21st-century learning approach identified to fit those needs. VR Cuisine is used as a teaching aid for basic special education modules of Western cuisine. The effectiveness of VR Cuisine as a teaching aid was studied on attitudes, behaviors, and skills among special needs students of the Basic Culinary Certificate, Selayang Community College, Malaysia. Qualitative methods through interviews and observations were conducted where differences in respondents’ behavior were observed and recorded to ensure the accuracy of the survey results. The study results found a positive increase in the game’s level of knowledge, behavior, and usefulness. Through observation, respondents have a high tendency to memorize movements and imitate game steps during real situations. In conclusion, using VR Cuisine as a teaching aid positively impacts changes in attitudes and behaviors among students with special needs. Game-based learning methods effectively create a more interesting, fun, interactive, and engaging learning environment.